Child Morbidity in Eastern Indonesia: Does Education and Smoking Behavior of Parents Influence it? (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
Child health is important, as it contributes to the child’s future. Indonesia was ranked second after India as a country with the highest tuberculosis (TB) cases. Well-educated parents must care for their children and maintain their health. At the same time, provinces in Eastern Indonesia have the lowest percentage of non-smoking areas (KTR) implementation. In this study, we analyzed the level of morbidity that focuses on respiratory disease, namely coughing and breathlessness in children. In addition, this study also analyzed the education and parents’ smoking behavior focused in Eastern Indonesia. The study analyzes child morbidity according to several affecting factors. Data used were cross-section data collected from secondary data from Indonesia Family Life Survey East (IFLS-East) in 2012. By applying the logistic regression analysis by logit and probit analysis, we figured out that parents’ education, children’s age, health service availability, and domicile area significantly influenced child morbidity. Fathers’ education played a crucial role, as the higher their education, the lower their children’s morbidity. Besides, we also found out that parents’ smoking habits, child immunization status, sex, and health insurance ownership did not significantly influence child morbidity. Fulfillment of educational aspects is required to the maximum until reaching adulthood, especially for unmarried individuals. Apart from that, parents of smokers and non-smokers need to be educated effectively on the dangers of smoking in order to create a healthy environment and the importance of tobacco or cigarette control policies in the Eastern part of Indonesia.